A unified Internet-delivered exposure treatment for undifferentiated somatic symptom disorder: single-group prospective feasibility trial - Jonna Hybelius; Anton Gustavsson; Sandra af Winklerfelt Hammarberg; Eva Toth-Pal; Robert Johansson; Brjánn Ljótsson; Erland Axelsson (Pilot and Feasibility Studies, 2022)
Abstract Background Exposure-based psychological treatment appears to have beneficial effects for several patient groups that commonly report distress related to persistent somatic symptoms. Yet exposure-based treatment is rarely offered in routine care. This may be because existing treatment protocols have been developed for specific symptom clusters or specific unwanted responses to somatic symptoms, and many clinics do not have the resources to offer all these specialised treatments in parallel. In preparation for a randomised controlled trial, we investigated the feasibility of a new and unified Internet-delivered exposure treatment (OSF.io: cnbwj) for somatic symptom disorder regardless of somatic symptom domain (e.g. cardiopulmonary, fatigue, gastrointestinal, pain), combination of unwanted emotions (e.g. anger, anxiety, fear, shame) and whether somatic symptoms are medically explained or not. We hypothesised that a wide spectrum of subgroups would show interest, that the treatment would be rated as credible, that adherence would be adequate, that the measurement strategy would be acceptable and that there would be no serious adverse events. Methods Single-group prospective cohort study where 33 self-referred adults with undifferentiated DSM-5 somatic symptom disorder took part in 8 weeks of unified Internet-delivered exposure treatment delivered via a web platform hosted by a medical university. Self-report questionnaires were administered online before treatment, each week during treatment, post treatment and 3 months after treatment. Results Participants reported a broad spectrum of symptoms. The Credibility/Expectancy mean score was 34.5 (SD = 7.0, range: 18–47). Participants completed 91% (150/165) of all modules and 97% of the participants (32/33) completed at least two exposure exercises. The average participant rated the adequacy of the rationale as 8.4 (SD = 1.5) on a scale from 0 to 10. The post-treatment assessment was completed by 97% (32/33), and 84% (27/32) rated the measurement strategy as acceptable. The Client Satisfaction Questionnaire mean score was 25.3 (SD = 4.7, range: 17–32) and no serious adverse events were reported. Reductions in subjective somatic symptom burden (the Patient Health Questionnaire 15; d = 0.90) and symptom preoccupation (the somatic symptom disorder 12; d = 1.17) were large and sustained. Conclusions Delivering a unified Internet-delivered exposure-based treatment protocol for individuals with undifferentiated somatic symptom disorder appears to be feasible. Trial registration ClinicalTrials.gov, NCT04511286 . Registered on August 13, 2020.